A community-based survey for different abnormal glucose metabolism among pregnant women in a random household study (SAUDI-DM). Issue 8 (19th August 2014) - Al-Rubeaan, Khalid; Al-Manaa, Hamad A; Khoja, Tawfik A; Youssef, Amira M; Al-Sharqawi, Ahmad H; Siddiqui, Khalid; Ahmad, Najlaa A
Abstract : Objective: To assess the prevalence and risk factors of gestational diabetes mellitus (GDM) in a population known to have a high prevalence of abnormal glucose metabolism. Methods: A household random population-based cross-sectional study of 13 627 women in the childbearing age, who were subjected to fasting plasma glucose if they were not known to have been diagnosed before with any type of diabetes. GDM cases were diagnosed using the International Association of Diabetes and Pregnancy Study Group (IAPSG) criteria. Results: The overall GDM prevalence was 36.6%, categorised into 32.4% new cases and 4.2% known cases. Another 3.6% had preconception type 1 or 2 diabetes. GDM cases were older and had a significantly higher body mass index, in addition to a higher rate of macrocosmic baby and history of GDM. Monthly income, educational level, living in urban areas and smoking were not found to be significantly different between normal and GDM cases. The most important and significant risk factors for GDM were history of GDM, macrosomic baby, obesity and age >30 years. However, hypertension, low high-density lipoprotein, family history of diabetes and increased triglycerides did not show any significant effect on GDM prevalence in this cohort. Conclusions: This society is facing a real burden of abnormal glucose metabolism during pregnancy, where almost half of the pregnant women are subjected to maternal and neonatal complications. Early screening of pregnant women, especially those at a high risk for GDM, is mandatory to identify and manage those cases.